2018
DOI: 10.1002/rcm.8073
|View full text |Cite
|
Sign up to set email alerts
|

Detection of the iron complexes with hydrolysis products of cephalexin and cefradine upon high‐performance liquid chromatography/electrospray ionization mass spectrometry analysis

Abstract: The detection of the complexes between the hydrolysis products of cephalosporins and iron may have a positive impact on the sensitivity and specificity of HPLC/ESI-MS analyses of the hydrolysis products of some cephalosporins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Hydrophobic interactions were supposed between the analyte and the adsorbents. To optimize the effect of carbon chain on the cephalosporins enrichment, three kinds of modifications, including C 2 , C 8 , and C 18 , were carried on for the MPS [31]. Quantitative determination of the carbon percentage for the MPS‐11 with different functional groups was achieved by the elemental analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Hydrophobic interactions were supposed between the analyte and the adsorbents. To optimize the effect of carbon chain on the cephalosporins enrichment, three kinds of modifications, including C 2 , C 8 , and C 18 , were carried on for the MPS [31]. Quantitative determination of the carbon percentage for the MPS‐11 with different functional groups was achieved by the elemental analysis.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to acid–base chemistry and the compound structure, the presence of metal ions, ,, minerals, and organic matter in surface waters is expected to influence the fate of β-lactam antibiotics. For example, previous studies have shown that Zn­(II), Cu­(II), ,,,, Co­(II), Mn­(II), and Fe­(III) , ions can promote hydrolysis of β-lactam antibiotics, as well as that the redox properties of the metal ion can promote oxidation of parent and transformation product compounds.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to acid–base chemistry and the compound structure, the presence of metal ions, ,, minerals, and organic matter in surface waters is expected to influence the fate of β-lactam antibiotics. For example, previous studies have shown that Zn­(II), Cu­(II), ,,,, Co­(II), Mn­(II), and Fe­(III) , ions can promote hydrolysis of β-lactam antibiotics, as well as that the redox properties of the metal ion can promote oxidation of parent and transformation product compounds. Furthermore, β-lactam antibiotics have been shown to adsorb to soil particles, including clays. , Adsorption to clay particles has been considered for β-lactam removal from wastewater solution. , Other antibiotic classes such as sulfonamides, tetracyclines, and fluoroquinolones, have been well studied with respect to their mechanisms of adsorption and degradation.…”
Section: Introductionmentioning
confidence: 99%